Broadly applicable hydrophilic additive enhances electrochemical transistor function - Lin Gao; Yongjoon Cho; Rui Wang; Yao Yao; Dayong Zhang; Yifan Wang; Yongfa Cheng; Yuyang Wang; Qing Ma; Isaiah Duplessis; Sein Chung; Evan Wilson; et al. (Proceedings of the National Academy of Sciences, 2026)
Organic semiconductors offering efficient mixed ionic-electronic charge transport are key components of organic electrochemical transistors (OECTs) needed for future bioelectronics and other technologies. However, hydrophobic semiconductors typically have limited ion mobility and are unstable in aqueous environments, restricting OECT applications. To address these issues, we report a broadly applicable strategy for high-performance OECTs by blending polymeric semiconductors with a photocrosslinkable hydrophilic ion-conducting supplement, poly(ethyleneglycol)-dimethylacrylate (PEGDMA). The result is ordered, interconnected semiconductor domains within an amorphous ion-conducting matrix, enabling rapid and reversible doping/dedoping without compromising charge transport. This approach enhances OECT performance across diverse electrolytes, semiconductors, and device architectures. Furthermore, PEGDMA enables high-resolution photopatterning of both semiconductors (<0.4 μm) and electrolytes (<2 μm), affording high-stability OECTs sustaining >10,000 cycles. This approach also enables wafer-scale array fabrication of 2,548 OECTs on 2” wafer, and miniaturized inverter, NAND, and NOR circuits. Also demonstrated are integration of these OECTs with a photosensor, creating a vision sensing array (10 × 10 pixels) that mimics visual image processing similar to the brain’s perception system.